Study on the Safety of the New Radial Artery Hemostasis Device. (5th April 2022) - Wu, Baofeng; Zhang, Ruixin; Liang, Chendi; Zhang, Chengjie; Qin, Gang
Abstract : Objective . At present, the use of particular radial hemostatic devices after coronary angiography (CAG) or percutaneous coronary intervention (PCI) has become the primary method of hemostasis. Most control studies are based on the products already on the market, while only a few studies are on the new hemostatic devices. The aim of this study is to compare a new radial artery hemostasis device which is transformed based on the invention patent (Application number: CN201510275446) with TR Band (Terumo Medical) to evaluate its clinical effects. Methods . In a prospective randomized clinical trial, 60 patients after CAG or PCI were randomly divided into two groups, patients in the trial group (CD group) using a new radial artery hemostasis device to stop bleeding and the control group (TR group) using the TR Band. The method is to collect relevant data of the two groups and compare the differences in hemostasis, local complications, and patient discomfort between the two groups. Results . The hemostatic devices in both groups achieved adequate hemostasis, and there was no failure to stop bleeding. The new radial artery hemostasis device was better than the TR band in pain and swelling (P < 0.05 ). There were no significant differences in bleeding, hematoma, ecchymosis, skin damage, and local infection between the two groups (P > 0.05 ). Conclusions . The sample of the new radial artery hemostasis device can stop bleeding effectively at the puncture site after CAG or PCI and is not inferior to the TR Band balloon hemostatic device in safety and is better in comfort.